Assistance of Tourism Cyber Public Relations in Increasing Publicity of Virtual Accessibility through Integrated Tourism Smart Platform (ITSP) in Wonokitri Tourism Village Pasuruan - Hakim, Lukman; Ahwan, Zainul; Rosadi, Muhammad Imron; Sanjaya, Cahya Bagus (LPPM Universitas Yudharta Pasuruan, 2024)
The hinterland area of Mount Bromo possesses exotic natural and cultural potential that can be developed into a leading tourist destination. However, the management and promotion of this potential face challenges, particularly in terms of tourism communication skills and the utilization of technology. The activity is to enhance the capacity of local tourism actors by mastering communication skills based on Tourism Cyber Public Relations and improving their ability to utilize technology to support more innovative and sustainable tourism services. Additionally, this program aims to facilitate the development of an integrated digital identity for the tourist village. The assistance program was carried out through five stages: socialization, training, technology implementation, mentoring, and sustainability evaluation. The approach employed was the Community Organizer and Community Development methods, with the main subject being the Raga Wulan Tourism Awareness Group in Wonokitri Village. The results of the activities showed a 25% increase in the knowledge of tourism actors based on pre-test and post-test results conducted during the program. Furthermore, this initiative successfully enhanced the tourism actors' skills in tourism communication, particularly in the field of Tourism Cyber Public Relations. It also resulted in the creation of branding and the development of social media and the official website of Edelweiss Wonokitri Tourism Village, as well as the realization of the Integrated Tourism Smart Platform.